2023
DOI: 10.1177/09697330231167542
|View full text |Cite
|
Sign up to set email alerts
|

Registered nurses’ exposure to high stress of conscience in long-term care

Abstract: Background In long-term care, registered nurses and other care providers often experience tensions between ideals and realities in the delivery of services, which can result in stress of conscience. Burnout, low quality of care and a tendency to leave the profession are perceived as consequences. Objectives This study aimed to identify the socio-demographic and work-related factors associated with a high level of stress of conscience, particularly between nursing occupations. Research design A cross-sectional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 50 publications
(114 reference statements)
0
1
0
Order By: Relevance
“… 32 Hence, it is essential to recognize these factors as important supportive measures in the regulations and rules boosting HMCS. In addition, it is noteworthy that the private lives of medical staff might remain an important factor, 33 albeit unassessed in our study. Haaland et al’s study identified nurses who experienced tensions between their responsibilities in home care service work and their family life, including concerns related to spending time with family and childcare.…”
Section: Discussionmentioning
confidence: 78%
“… 32 Hence, it is essential to recognize these factors as important supportive measures in the regulations and rules boosting HMCS. In addition, it is noteworthy that the private lives of medical staff might remain an important factor, 33 albeit unassessed in our study. Haaland et al’s study identified nurses who experienced tensions between their responsibilities in home care service work and their family life, including concerns related to spending time with family and childcare.…”
Section: Discussionmentioning
confidence: 78%
“…The doors had to be locked, and restrictions prevented older persons and their families from coming and going as they wished. Furthermore, RNs are nearly twice as likely to report high stress of conscience compared with other staff in long-term care [39].…”
Section: Discussionmentioning
confidence: 99%